Maternal immune response and air pollution exposure during pregnancy: insights from the Early Markers for Autism (EMA) study - Heather E. Volk (Journal of Neurodevelopmental Disorders, 2020)
Abstract Background Perinatal exposure to air pollution and immune system dysregulation are two factors consistently associated with autism spectrum disorders (ASD) and other neurodevelopmental outcomes. However, little is known about how air pollution may influence maternal immune function during pregnancy. Objectives To assess the relationship between mid-gestational circulating levels of maternal cytokines/chemokines and previous month air pollution exposure across neurodevelopmental groups, and to assess whether cytokines/chemokines mediate the relationship between air pollution exposures and risk of ASD and/or intellectual disability (ID) in the Early Markers for Autism (EMA) study. Methods EMA is a population-based, nested case–control study which linked archived maternal serum samples collected during weeks 15–19 of gestation for routine prenatal screening, birth records, and Department of Developmental Services (DDS) records. Children receiving DDS services for ASD without intellectual disability (ASD without ID; n = 199), ASD with ID (ASD with ID; n = 180), ID without ASD (ID; n = 164), and children from the general population (GP; n = 414) with no DDS services were included in this analysis. Serum samples were quantified for 22 cytokines/chemokines using Luminex multiplex analysis technology. Air pollution exposure for the month prior to maternal serum collection was assigned based on the Environmental Protection Agency’s Air Quality System data using the maternal residential address reported during the prenatal screening visit. Results Previous month air pollution exposure and mid-gestational maternal cytokine and chemokine levels were significantly correlated, though weak in magnitude (ranging from − 0.16 to 0.13). Ten pairs of mid-pregnancy immune markers and previous month air pollutants were significantly associated within one of the child neurodevelopmental groups, adjusted for covariates (p < 0.001). Mid-pregnancy air pollution was not associated with any neurodevelopmental outcome. IL-6 remained associated with ASD with ID even after adjusting for air pollution exposure. Conclusion This study suggests that maternal immune activation is associated with risk for neurodevelopmental disorders. Furthermore, that prenatal air pollution exposure is associated with small, but perhaps biologically relevant, effects on maternal immune system function during pregnancy. Additional studies are needed to better evaluate how prenatal exposure to air pollution affects the trajectory of maternal immune activation during pregnancy, if windows of heightened susceptibility can be identified, and how these factors influence neurodevelopment of the offspring.